Impacts and challenges of Artificial Intelligence in Medicine: An updated literature review (Research, Society and Development, 2024)
Artificial Intelligence (AI) has been increasingly used in medicine through tools that promise advances in medical practice. As it is a recently popularized technology, there is still much debate about its impacts and even more about the challenges to be faced in the healthcare field. In view of this, the present study aims to understand the impacts of AI in medicine and the challenges for its consolidation in the medical context. A literature review was carried out based on 10 scientific articles published from 2019 to 2024, in English, Portuguese and Spanish, selected from the Virtual Health Library, Lilacs, PubMed and SciELO databases using the health descriptors “Artificial Intelligence”, “Medical Education” and "Health". The literature points out the impacts of AI in medicine, which includes advances in access to and processing of health data, in the interpretation of exams, in procedures and in medical decision-making. The use of AI tools is also evidenced both in the education of young doctors and in clinical practice and in the approach to new specialties. However, challenges for the use of AI in the medical field are also highlighted, related to technical, ethical and legal aspects. It is clear that AI has beneficial impacts for patients and professionals in training or working, but its consolidation in medicine still faces important challenges marked by the lack of knowledge of the yet unexplored limits of this technology.